Systematic risk variations (beta) convertible debenture brazilian companies - Renata Drumond Pinto Coelho Antonino; Wagner Moura Lamounier; Roberto Kaehler de Albuquerque Maranhão (BBR: Brazilian Business Review)
purpose of this article is to analyze the impact of issuing convertible debentures on the systematic risk of Brazilian companies. Some applied researches in the U.S. capital market (STEIN, 1992; LEWIS et al, 2002; RAI, 2005) indicate that convertible debentures may be used as an alternative financing source when adverse selection problem makes stock issuing unattractive financing source. The analysis of Brazilian companies that issued convertible debentures recorded in the period from 1998 to 2006 and that presented liquidity on the market indicated that variation in beta, on average, is positive. These results are coherent with the signaling hypothesis and with the absence of convertible debenture issuing in 2005 and 2006 on the Brazilian market. They also may be related to the precarious financial situation of issuing companies, observed by the analysis of some financial indicators in year of issue and in two pre- e post-issuing years.